3rd order microstrip symmetrical DBR filter at 5GHz / Hasif Mohamad - Mohamad, Hasif (2010)
This research reports on the design of 3r order microstrip symmetrical dual-behaviour resonators (DBRs) filter. The filter is centered at 5 GHz. The DBR filter is designed on FR4 substrate (dielectric thickness h=1.6mm, relative permittivity sr = 5.4). Throughout the paper, simulations are proposed to illustrate the possibilities offered by the idea. Experimental results in microstrip technology are also presented in order to validate the idea. Lastly, benefit and drawbacks of the design are discussed.